Updated peer review of the pesticide risk assessment for the active substance dithianon in light of confirmatory data submitted. (10th September 2020) - ,; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Brancato, Alba; Bura, Laszlo; Carrasco Cabrera, Luis; Chaideftou, Eugenia; Chiusolo, Arianna; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State, Greece, for the pesticide active substance dithianon are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory mammalian toxicology and residues data. The conclusions were reached on the basis of the evaluation of the representative uses of dithianon as a fungicide on table and wine grapes and on pome fruit. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Concerns are identified.